2021
DOI: 10.3390/electronics10141625
|View full text |Cite
|
Sign up to set email alerts
|

Counter-Passive Coherent Locator (C-PCL)—A Method of Remote Detection of Passive Radars for Electronic Warfare Systems

Abstract: Passive Coherent Location methods and techniques have an established position in the modern state-of-the-art radar. Inexpensive, easy to deploy and undetectable for other sensors, passive radars are growing in popularity. Due to that, a need arises to develop proper methods of any possible kind of countermeasure. In this work, a method of detection and localization of hidden PCL systems is proposed. Authors exploit certain physical features of an RF receiver in order to detect such a passive systems. Results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Due to the threat posed by man-portable passive infrared homing SAMs, passive missile warning systems have been developed to sound an alarm as soon as a missile engages an aircraft [6]. Once a missile is fired at the aircraft, the missile approach warning system (MAWS) detects the threat and displays a warning on display within a short time (on the order of a few milliseconds), referred to as detection time.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the threat posed by man-portable passive infrared homing SAMs, passive missile warning systems have been developed to sound an alarm as soon as a missile engages an aircraft [6]. Once a missile is fired at the aircraft, the missile approach warning system (MAWS) detects the threat and displays a warning on display within a short time (on the order of a few milliseconds), referred to as detection time.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the use of passive radar that utilizes existing signals in the environment as illuminators of opportunity (IoOs) has gained attention in the academic and military fields due to its capability to detect targets without revealing the location of the sensor, because it does not emit radar signals [ 1 ]. Therefore, its receiver is much less susceptible to electronic countermeasures (ECM) [ 2 ], and its intrinsic bistatic operation has anti-stealth capabilities. Furthermore, as it is completely passive, deploying the receiver does not need frequency allocation, making it usable in densely populated areas where electromagnetic interference can be a problem, nor does it require a careful transmit beamforming design to avoid interception [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…While interest in the use of passive systems continues to grow as a result of their ability to function without a dedicated active transmitter and their resilience to electronic counter-measures (ECM), the general limitations on the availability of research on the subject of ECM against passive radar systems within open literature is highlighted in [14] and [15]. It is also suggested that deception jamming methods are of limited use against passive systems [16], demonstrating the need for systems with integrated passive capabilities but also validating the necessity for continued innovation to combat noise based jamming techniques, though the viability of deception jamming usage against networks involving passive pairs is disputed [17].…”
Section: Introductionmentioning
confidence: 99%